Pembrolizumab‐induced sarcoid granulomatous panniculitis and bullous pemphigoid in a single patient. Issue 4 (11th March 2019) - Honigman, Anthony D.; Lai, Franics; Elakis, Joshua; Prall, Owen; Goh, Michelle; McCormack, Christopher
Key Clinical Message: Pembrolizumab is an immune checkpoint inhibitor with antitumor activity in other organ malignancies. We present this case —demonstrating multiple inflammatory adverse events associated with Pembrolizumab (in a single patient), in order to increase awareness and facilitate earlier identification of the wide‐ranging cutaneous side effects associated with immunotherapy. Abstract : Pembrolizumab is an immune checkpoint inhibitor with antitumor activity in other organ malignancies. We present this case —demonstrating multiple inflammatory adverse events associated with Pembrolizumab (in a single patient), in order to increase awareness and facilitate earlier identification of the wide‐ranging cutaneous side effects associated with immunotherapy.